EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PADI KECAMATAN TABUKAN KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Dessyana Ayu Eka Tristanti; Eva Alviawati; Ellyn Normelani (JPG (Jurnal Pendidikan Geografi), 2016)
The title of this research is "The Evaluation of Land Suitability for Rice in subdistrict of Tabukan, Barito Kuala regency, South Kalimantan". This study aims to determine the class of land suitability for agricultural land in the subdistrict of Tabukan Barito Kuala.The population and sample of this research are in the form of 14 units of land in subdistrict of Tabukan, which is obtained from the overlap, Notching Land Map, Land Use Map, Soil Map, and Slopes Map.The primary data was obtained through observations in the field, as well as taking soil samples that will be analyzed either directly through the laboratory. Secondary data were obtained from the study of documents and literature. Data analysis technique used was matching and scoring.The results of this research of rice land suitability evaluation using matching method states that the land suitability class S3 (based on marginal) for rice, with the factor of limitation, those are, temperature (T), base saturation (Bs), P2O5, (n), and consistency of big grain soil (p). As for the scoring method for the land suitability class rice  is S1 (very suitable) with the interval of land suitability interval between 110 up to 130. Keywords: Evaluation of land suitability, rice plant, scoring, matching,